IGF-I receptor and thyroid-associated ophthalmopathy - Mohyi, Michelle (J Mol Endocrinol, 2017)
Thyroid-associated ophthalmopathy (TAO) is a vexing and poorly understood autoimmune process involving the upper face and tissues surrounding the eyes. In TAO, the orbit can become inflamed and undergo substantial remodeling that is disfiguring and can lead to loss of vision. These are currently no approved medical therapies for TAO, the consequence of its uncertain pathogenic nature. It usually presents as a component of the syndrome known as Graves’ disease where loss of immune tolerance to the thyrotropin receptor (TSHR) results in the generation of activating antibodies against that protein and hyperthyroidism. The role for TSHR and these antibodies in the development of TAO is considerably less well established. We have reported over the past 2 decades evidence that the insulin-like growth factor-I receptor (IGF-IR) may also participate in the pathogenesis of TAO. Activating antibodies against IGF-IR have been detected in patients with GD. The actions of these antibodies initiate signaling in orbital fibroblasts from patients with the disease. Further, we have identified a functional and physical interaction between TSHR and IGF-IR. Importantly, it appears that signaling initiated from either receptor can be attenuated by inhibiting the activity of IGF-IR. These findings underpin the rationale for therapeutic targeting IGF-IR in active TAO. A recently completed therapeutic trial of teprotumumab, a human IGF-IR inhibiting antibody, in patients with moderate to severe, active TAO, indicates the potential effectiveness and safety of the drug. It is possible that other autoimmune diseases might benefit also benefit from this treatment strategy.